Collaboration language learning and teaching - Collaboration language learning and teaching (Cambridge Univ. Press, 1992)
This book provides a rationale for collaborative learning and teaching. It describes: * central characteristics of a collaborative approach to classroom research * appropriate theoretical methods of language and learning for infoeming collaborative research * appropriate research methods, tools and techniques for collaborative investigations * organisational patterns underlie successful collaborative teaching